An In Vivo Comparison of Trueness and Precision of Two Novel Methods for Improving Edentulous Full Arch Implant Scanning Accuracy: A Pilot Study - Adam Brian Nulty (Dentistry Journal)
Background: This retrospective in vivo study evaluated the trueness and precision of two digital intraoral scanners—Dentsply Sirona Primescan and Medit i900—, both with and without two variants of the novel Scan Ladder aids, and compared their performance to a new intraoral photogrammetry scanner (Shining 3D Elite). Methods: Data from ten edentulous patients, previously collected during routine clinical treatment, were analyzed using a master STL generated from traditional impression casts as the reference. A custom positional change calculator and comprehensive statistical analysis were used to assess scanner accuracy. Results: The findings demonstrated that the use of the Scan Ladder significantly enhanced the overall accuracy of both intraoral scanners, showing no statistically significant differences when compared to the intraoral photogrammetry system. Conclusions: These results indicate that the Scan Ladder improves the performance of conventional intraoral scanners and suggests that the Shining 3D Elite intraoral photogrammetry scanner is a reliable alternative to extraoral photogrammetry for edentulous cases. Further research, with a larger and more diverse cohort, is warranted to validate and expand upon these findings.